2020
DOI: 10.1186/s12871-020-01180-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intraoperative cerebral oximetry and postoperative delirium in patients undergoing off-pump coronary artery bypass graft surgery: a retrospective study

Abstract: Background Cerebral oximetry has been widely used to measure regional oxygen saturation in brain tissue, especially during cardiac surgery. Despite its popularity, there have been inconsistent results on the use of cerebral oximetry during cardiac surgery, and few studies have evaluated cerebral oximetry during off pump coronary artery bypass graft surgery (OPCAB). Methods To evaluate the relationship between intraoperative cerebral oximetry and postoperative delirium in patients who underwent OPCAB, we inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It is supported by previous studies which showed that brain hypoxemia during surgery was associated with postoperative delirium (21)(22)(23). Wang et al (32) used the rSO2 desaturation score, calculated based on baseline rSO2 and changes in rSO2 over time (39)(40)(41), and showed that the rSO2 desaturation score was associated with postoperative delirium. Similar results were observed in patients undergoing cardiac surgery (42).…”
Section: Discussionmentioning
confidence: 68%
“…It is supported by previous studies which showed that brain hypoxemia during surgery was associated with postoperative delirium (21)(22)(23). Wang et al (32) used the rSO2 desaturation score, calculated based on baseline rSO2 and changes in rSO2 over time (39)(40)(41), and showed that the rSO2 desaturation score was associated with postoperative delirium. Similar results were observed in patients undergoing cardiac surgery (42).…”
Section: Discussionmentioning
confidence: 68%
“…The duration of rSO 2 < 50% was 40% longer in patients with POD. For the prediction of POD, the cut-off value of intraoperative rSO 2 was 50% for the total patient population, and 55% for patients younger than 68 years (39). Cournoyer et al included 20 non-randomized studies in patients after cardiac arrest and concluded that a higher regional cerebral saturation is associated with improved resuscitation outcomes, especially the return to spontaneous circulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies reported that patients with low preoperative cerebral oxygen saturation had a higher incidence of postoperative delirium 184,185 ; intraoperative cerebral oxygen desaturation was associated with increased postoperative delirium. [62][63][64] A pairwise and network meta-analysis included 12 randomized trials with 1626 patients investigating the effect of brain near-infrared spectroscopy-based intervention; the results showed that cerebral oxygenation-guided management reduced delirium after cardiac surgery but not major noncardiac surgery. 186 Cerebral oxygenation-guided management may be helpful in patients undergoing cardiac surgery.…”
Section: Monitoring Of Cerebral Oxygen Saturationmentioning
confidence: 99%